“Colocando as miçangas na guia”: o pesquisar em saúde nos terreiros de umbanda - Severo, Ana Kalliny de Sousa (2019)
The field of health has historically allowed little participation of the peoples of terreiros both from their practices of planning, implementing, evaluating and managing health care as well as from their research activities. The present article aims to discuss the methodological strategies and also the challenges in the execution of a research carried out in three terreiros of Umbanda in the city of interior of Piauí and in the consequent Family Health Strategies that cover these sacred establishments. With this study, it is intended that from the sharing of an investigative experience contrary to the perspectives that underpin the idea of the “researcher-expert", guidelines should be established for future academics and researchers in the field of health who intend to carry out studies in terreiros of Umbanda